Zur Prädiktabilität von Interferenzen im Lichte einer Testanalyse - Czochralski, Jan (Studia Germanica Posnaniensia, 2018)
The article is the analysis of typical interference errors, based on the conducted translation test, concerning the usage of tense forms of German verbs. The author draws conclusions as for the possibility of predicting such errors. He also suggests methods of overcoming these mistakes by Poles studying the German language.